Les jardins des « châteaux de la Seine », du XVIIIe siècle à nos jours : métamorphoses et disparitions - Andrea Baserga; Jérémie David (Les Cahiers de l'École du Louvre)
In the eighteenth century, a series of chateaux, now no longer extant or heavily modified, lined the Seine in the Paris region. The gardens of these chateaux comprise excellent entry points for the study of the transformation of these landscapes. The gardens and their chateaux, which in turn reflect changes in taste, social developments and economic constraints, also provide an insight into the metamorphosis of landscapes in the Paris region. By studying the disappearance of these chateaux, Andrea Baserga and Jérémie David propose a history of art that makes disappearance a key stage in the itinerary of monuments and goes back to the sources of this process.